Spirit cure: a history of pentecostal healing - Williams, Joseph W. (Oxford University Press, 2013)
Joseph W. Williams examines the changing healing practices of pentecostals in the United States over the past 100 years, from the early believers, who rejected mainstream medicine and overtly spiritualized disease, to the later generations of pentecostals and their charismatic successors, who dramatically altered the healing paradigms they inherited. Williams shows that over the course of the twentieth century, pentecostal denunciations of the medical profession often gave way to "natural" healing methods associated with scientific medicine, natural substances, and even psychology. By 2000, figures such as the pentecostal preacher T. D. Jakes appeared on the Dr. Phil Show, other healers marketed their books at mainstream retailers such as Wal-Mart, and some developed lucrative nutritional products that sold online and in health food stores across the nation. Exploring the interconnections, resonances, and continued points of tension between adherents and some of their fiercest rivals, Spirit Cure chronicling adherents` embrace of competitors` healing practices and illuminates pentecostals` dramatic transition from a despised minority to major players in the world of American evangelicalism and mainstream American culture.